Pengembangan Multimedia Pembelajaran Materi Radioaktif Menggunakan Swish Max 4 untuk SMA Kelas XII IPA - Muhammad Damris; Syamsurizal Syamsurizal; Eliza Yuliani (Pendidikan Kimia FKIP Universitas Jambi, 2017)
Chemical learning that is boring and unattractive makes students less interested in learning. For that developed multimedia learning by using software Swish Max 4. The purpose of this study was to develop multimedia learning using Swish Max 4 on radioactive and to know its impact on the learning experience of students at class XII IPA SMA N 8 Kota Jambi. This study is a development study that adapts the ADDIE model. Stage in the development research are analysis, design, development and evaluation. Instrument sheets used collecting data were questionnaire of student needs, media validation questionnaire,material validation questionnaire, teacher assessment questionnaire and students response questionnaire. The main result of this study is a multimedia learning on radioactive using Swish Max 4, that equipped with video and animation. This multimedia learning on radioactive is good based on validation results from media experts and material experts. From the results of product trials of chemistry teachers and students response at Class XII IPA SMA N 8 Jambi, this media can be used to help students in learning independently. Based on the results of study concluded that multimedia learning on radioactive using Swish Max 4 is good for use in learning and get student response to multimedia learning is very good with score 82,4%.